Exploring Industry 4.0’s Role in Sustainable Supply Chains: Perspectives from a Bibliometric Review - Federico Briatore; Francesca Vanni; Marco Tullio Mosca; Roberto Nicola Mosca; Fabio Fruggiero; Francesco Mancusi (Logistics)
Background: Industry 4.0 (I4.0) technologies have transformed supply chain (SC) logistics and production. However, their environmental impact, particularly on CO2 emissions and carbon footprints, remains underexplored. This study examines the impact of I4.0 tools on SCs sustainability, focusing on reducing carbon footprints. Methods: A bibliometric analysis was conducted in October 2023 to quantitatively evaluate the scientific literature, examining publication characteristics to assess current research and forecast future trends. The Scopus database was utilized with specific filters to identify studies on the impact of I4.0 technologies in SC domains on sustainability, focusing on CO2 emissions and carbon footprint reduction. VOSviewer software version 1.6.15 was used to analyze selected papers, revealing key keyword clusters and relationships. Results: Five clusters were identified, offering insights for supply chain managers and highlighting links between I4.0 and CO2 reduction in supply chains: “LCA towards zero carbon”, “Supply chain carbon footprint”, “Risk and decarbonization analysis”, “Industry 4.0 and stochastic models for sustainability”, and “Biodiversity and environmental impact”. Key findings emphasize the strong connection between LCA, carbon footprint analysis, emission control, and the role of I4.0 technologies like blockchain and IoT in reducing emissions. Conclusions: This study highlights the environmental benefits of I4.0 in SC management, supporting global decarbonization goals.